다문화가정 결혼이주여성의 출신 국가에 따른 식생활행동 조사 - 김정현(Jung-Hyun Kim); 이명희(Myung-Hee Lee) (Korean journal of community nutrition, 2016)
Objectives: Nowadays, the multicultural families make up significant portion of Korean population and communities. Successful re-settling in a new country can be difficult, particularly when there are disparities in dietary behavior compared to home country. The objective of the study was to investigate the dietary behavior of marriage migrant women according to their nationality in multicultural families. Methods: The primary research was conducted targeting 94 marriage migrant women who came from China (40.4%), Vietnam (26.6%), and other countries except for Japan (33.0%). We investigated their dietary behavior, such as eating attitude and food choice behavior for Korea acculturation. We also studied dietary behavior among 14 selected subjects who had high level of integration and assimilation acculturation patterns by administering the Focus Group Interview (FGI). Results: The multicultural families had more integration acculturation patterns, which could have been influenced by their nationality. Vietnamese origin has the highest cultural adaptation as marginalization pattern. The common types of Korea acculturation were integration ($3.03{±}1.08$), separation ($3.10{±}0.59$), marginalization ($3.10{±}0.58$), followed by assimilation ($2.84{±}0.51$). There were significant differences in the four types of acculturation by marriage immigrant women's country of origin (p<0.05). According to dietary behavior, 'eliminating hunger' was the most important value in a meal. Chinese marriage migrant women, who had higher level of food intake attitude significantly, also considered 'being healthy' an important value. Regarding food choice behavior, Vietnamese had lowest frequency of homeland food intake. Most of marriage immigrant women were satisfied with the Korean food, and need for education was very high with interest for cooking, good nutrition, and managing their children's dietary life. Conclusions: Coping with a change in dietary behavior is one of the biggest transitional difficulties, and family members may need support to find their familiar food items and to continue their cultural food choice behavior in the local areas. Further researches with quantitative and qualitative analysis are needed to understand the effect of dietary behavior for acculturation in multicultural families.